IMAGE ENHANCEMENT CITRA DIGITAL SHORT PIN PWR FUEL BERISI PELET UO2 ALAM PASCA UJI RADIOGRAFI SINAR-X MENGGUNAKAN PROGRAM IMAGEJ - Artika, Refa; Sigit, Rohmad; Ajiriyanto, Maman Kartaman; Yulianto, Tri (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Non-destructive test using digital X-ray radiography is one of the important series in performance evaluation of nuclear materials and fuels. Image enhancement or image quality improvement is needed for further analysis of digital X-ray radiography images which tend to have lower resolution. Image enhancement process on digital x-ray radiographic images needs to be carried out to provide images that are easier to interpret so that the resulting data can be used as a basis for evaluating performance after irradiation. The tests were performed at a distance of 40 cm against the detector at voltage and current of 120 kV and 1000 μA. The image enhancement was later performed using ImageJ, which involves the process of aligning the image contrast, edge enhancement, processing histogram value, and adjusting image colors. The resulted data were costumized according to the information to be obtained from the digital X-ray radiography test such as dimensional data, boundaries between pellet, and histogram ilustrating material or thickness differences. Further, this information can be used as data input in mapping the concept of enhancement of image of short pin PWR fuel contains UO2 pellets. Output image produced from the enhancement process not only has a better resolution and quality to facilitate the process of analysis and interpretation but also can be used as a standard method to perform image enhancement of digital X-ray radiography images of short pin PWR fuel contains UO2 pellets after irradiation.